An Authentic Inner Compass and Need Satisfaction as Wellbeing Resources in Bedouin Teaching Students During the COVID-19 - Cohen, Rinat; Slobodin, Ortal (Frontiers in Psychiatry, 2022)
A growing body of literature suggests that students from underserved backgrounds are more vulnerable to the adverse economic, emotional, and academic effects of the current COVID-19 pandemic. While this vulnerability was attributed to multiple structural and socio-cultural barriers, little attention has been paid to the role of psychological resources in preserving well-being in times of crisis and change. Guided by the Self-Determination Theory (SDT), the current study examined the role of the authentic inner compass (AIC) and need-satisfaction in predicting the well-being of Bedouin students attending teachers' higher education institutes in the south of Israel during the COVID-19. Participants were 84 college Bedouin teaching students (84.1% female) who completed online questionnaires addressing the sense of AIC, need-based experiences, psychological distress, and positive affect. Consistent with the propositions of the SDT, we found that a strong and clear sense of AIC, as well as high need satisfaction and low need frustration, were associated with lower distress and higher positive effect in Bedouin teaching students. We have also found that need satisfaction moderated the effect of the AIC on students’ well-being so that AIC better predicted lower distress and higher positive effect when students' levels of need satisfaction were higher. Our findings lend further support to the importance of the AIC and need satisfaction to optimal functioning even in collectivist cultural contexts that do not prioritize values of autonomy. The current study provides insight into the interplay between AIC and need-based experience by describing the conditions under which AIC may be beneficial for well-being in times of crisis.